FOREIGN DIRECT INVESTMENT, TINGKAT PENGANGGURAN, DAN KESENJANGAN PENDAPATAN Studi Time Series di Indonesia Periode 2002-2015 - Muhammad Rheza Ramadhan (E-Mabis: Jurnal Ekonomi Manajemen dan Bisnis, 2018)
This research is a time-series study in 2002-2015 year which aim to find the effect of Foreign Direct Investment to Unemployment Rate and Income Inequality. Base on a hand-collected sample in 2002-2015, our regression result show that Foreign Direct Investment positively associated with income inequality and did not associate with unemployment rate after controlling for inflation and government expenditure effect.